Naphthalen-2-yl-N′-(2-hydroxybenzoyl)benzohydrazonate as dual metal ion chemosensor for the detection of Fe3+ and Na+ ions - P. Kalaivani; R. Lokeshwari; R. Shankar; S. Cyril Christan; R. Prabhakaran (Chemistry of Inorganic Materials)
New probe naphthalen-2-yl-N′-(2-hydroxybenzoyl)benzohydrazonate (NHBH) chemosensor has been prepared and characterized by IR, 1H NMR, 13C NMR and Mass Spectroscopic techniques. The probe (NHBH) was subjected to study its cation sensing ability with twelve different metal chloride salt (Al3+, Ca2+, Co2+, Cr3+, Fe3+, Cu2+, Mn2+, Ni2+, Zn2+, Hg2+, K+ and Na+) in 1:4 methanol water medium by using absorption and emission titration experiments. The results showed that the probe detected Fe3+ and Na ​+ ​ions by showing absorption enhancement and fluorescence emission quenching. Further, NHBH exhibited good selectivity for Fe3+ and Na ​+ ​ions in the presence of mostother metal ions. Job's plot analysis authenticated the 1:1 binding nature of NHBH with Fe3+ and Na ​+ ​ions. Further, DFT studies validated the formation of probe (NHBH), fluorophore-quencher (Fe-NHBH) complex formation.